Optimization of Marketing Mix to Increase the Competitiveness of Savira Frozen Food in the Local Market - Agustin Rani Nurfadila; Arief Rahmawan; Palmadi Putri Surya Negara; Bayu Wahyudi; Much. Taufik Ardani (Universitas Darussalam Gontor, 2024)
Frozen food is a product that is frozen to extend its shelf life. Currently, this product is in demand by many people. This study aims to identify the marketing mix of Savira Frozen Food and analyze internal and external factors in its business development strategy. The methods used are qualitative surveys and direct interviews with business owners to obtain qualitative data on the business and analyzed using SWOT. Based on the results of the study, it can be concluded that the 4P marketing mix implemented by Savira Frozen Food Ponorogo MSMEs such as (a) the products produced are of good quality, (b) the price is determined by the price of competitors, (c) it is located in a strategic place, and (d) the promotions that have been implemented by Savira Frozen Food Ponorogo MSMEs are carried out by face-to-face sales and individual sales. This business development strategy is first, maintaining product variants and quality so that consumers are more interested in the products produced; second, changes in people's consumption patterns are opportunities that must be taken advantage of; third, utilizing coolers so that they can meet consumer desires; fourth, increasing the number of employees and making financial records and the existence of easy-to-obtain raw materials so that production runs smoothly; fifth, adding product innovation so that it can maintain its competitiveness in the market and consumers are free to choose products; And sixth, increase advertising by using social media so that it can maintain its competitiveness in the market